The Ontology of Legal Science: Hans Kelsen’s Proposal of the ‘Pure Theory of Law’ - Kelik Wardiono; Khudzaifah Dimyati; Saepul Rochman (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
Through the pure legal theory, within the thesis of normativity (without the thesis of morality) and the thesis of separation (without the thesis of reductive), Hans Kelsen proposes an object of legal science that is different from the one proposed by the philosophy schools of natural law and empirical-positivistic law. The idea transforms the legal science into a unique and distinctive science. Based on the philosophical research method, a legal norm, according to Hans Kelsen, must have two characters: the meaning of actions that want legal norm; and the relative moral norms with normative characteristics.Ontologi Ilmu Hukum: Tawaran Hans Kelsen dalam ‘Pure Theory of Law' AbstrakDi dalam pure theory of law, melalui tesis normativitas (tanpa tesis moralitas) dan tesis keterpisahan (tanpa tesis reduktif), Hans kelsen menawarkan objek ilmu hukum yang berbeda dengan madzhab filsafat hukum alam, dan madzhab filsafat hukum empiris–positivistik, sehingga ilmu hukum memiliki objek ilmu yang khas. Berdasarkan metode penelitian filsafat, dapat diketahui bahwa norma yang dapat menjadi norma hukum menurut Hans Kelsen, harus memiliki dua karakter yaitu norma hukum sebagai makna tindakan berkehendak norma hukum, sebagai norma moral relatif yang berkarakter normatif.DOI: https://doi.org/10.22304/pjih.v5n3.a8